The Application of Media Sibi and Rainbow Flag to Enhancement Locomotor Motion and Manipulative Motion of Deaf Disability Children on Basketball Material - Harries Tri Mada; Dwi Cahyo Kartiko; Gigih Siantoro (BIRCU, 2020)
Everyone is entitled to education because education serves to improve the quality of a person's life. Education for deaf disability children, also needs to get focused of attention according to the limitations basic motor motion. The application of adaptive aplication learning media is used to improve motor skills of the disabled child's motor disability.The purpose of this research is to find out about: (1) the impact of application of media SIBI can help locomotor motion of deaf disability children, (2) the impact of media SIBI application to help manipulative motion of deaf disability children, (3) the impact of application of rainbow flag to help locomotor motion of deaf disability children, (4) the impact of the application of rainbow flags to help manipulative motion deaf disability children, (5) the magnitude of the increase in locomotor activity of deaf disability children using the application of media SIBI and rainbow flag, (6) the increase in manipulative activity of deaf disability children using the application of media SIBI and rainbow flags.This research is quantitative with quasi-experimental. The research design uses matching-only design, data analysis using Paired-Sampels T Test. The process of data collection is done with a pretest and posttest weight using the instrument of adapted motor skills, and validated by the expert to retrieve data locomotor motion and manipulative motion.The result of data analysis using SPSS version 20 on average data between pretest and posttest each group, namely: (a) Locomotor: media SIBI group increased 10,10%, sig. = 0.003 and the rainbow flag group increased 13.40%, sig. = 0.001. (b) Manipulative: media SIBI group increased by 10.10%, sig. = 0.063 and the rainbow flag group increased 13%, sig. = 0.007. Is increasing the influence of media SIBI and rainbow on locomotor motion 11,75% while in motion manipulative 11,55%.The result of the the study, that the application of media SIBI to improve locomotor motion not for manipulatif motion behind rainbow flag to improve of locomotor motion and manipulative deaf disability children.One of the fundamental strategies in attempts to develop athletic sports in Surabaya was to conduct special training through athletic extracurricular activities in schools, hence it was the starting point for the discovery of potential athletes. The purpose of this study was to determine the strengths, weaknesses, opportunities, and Threat from athletic extracurricular management which included Planning, Organizing, Implementing and Supervising which was conducted by Dr. Soetomo and Jalan Jawa Junior High School in Surabaya. The approach used in this study was a qualitative approach and the type of evaluative research (Evaluation Research) used descriptive methods. The evaluation design used in this study was the SWOT Analysis. The results and conclusions of this study indicated that the athletic extracurricular management at Dr Soetomo Junior High School; The Planning was already a good program, The Organizing used the organizational structure and cooperation which already existed so the working mechanism was clear of its functions and parts, The Actuating contained the schedule of activities, the attendance of students and the coaches are well-monitored by the extracurricular coordinator, The Controlling implemented a routine evaluation that carried out at the end of the school year, but for the achievements have not been as the expectation. On the other hand, Jalan Jawa Junior High School implemented the management as; The Planning of this school did not have a good program, The Organizing included the involved cooperation of leaders, teachers and parents of students was very good, The Actuating related to the exercise did not run well, The Oversight represented almost every championship in Surabaya, Jalan Jawa Junior High School got good marks. The researchers have conducted more in-depth analysis of the strengths, weaknesses, opportunities, and Threat of athletic extracurricular management which included Planning, Organizing, Implementing and Supervising which was conducted by Dr Soetomo and Jalan Jawa Junior High School in Surabaya, furthermore resulting some recommendations for Dr. Soetomo and